Illustrated History of Great Britain - Clark, Sir George; Edited and with Additional Material by Westwood, J.N. (Oxford, New York Oxford University Press, 1987)
First published as part of the best-selling The Oxford Illustrated History of Britain, John Morrill's Very Short Introduction to Stuart Britain shows how in the Stuart century, a century of Revolution, political, religious, social, and economic changes came together
Include Illustration and Index
Keywords: Great Britain